Gendered relations and time-use perspectives from selected households of Philippines’ Pantawid Pamilyang Pilipino Program in Calauan and San Pablo City, Laguna - Alinsunurin, Maria Kristina G. (2018)
On meeting education and health targets, conditional cash transfer programs are consistent with their intended development impacts. However, gendered outcomes remain to be in the periphery of the discourse. This paper aims to analyze the gender relations within cash transfer program households, focusing on the Pantawid Pamilyang Pilipino Program (4Ps). Through a time-use analysis approach and using qualitative information from in-depth household interviews and observations, the study examines how women grantees use their time and how this reflects gendered elements on intra-household relations. Results reveal that a) meeting program co-responsibilities have an impact on their household tasks, especially in supporting children’s education and b) despite the transfers, gender and power dynamics within the household remain the same. This research contributes to the ongoing policy discourses on cash transfers and women’s participation.
Keywords: Gender role; Pantawid Pamilya Pilipino Program